Correction to: The effect of moderate intermittent versus continuous energy restriction on body composition and resting metabolic rate in resistance-trained females: A randomized controlled trial. Issue 1 (29th December 2020) - Siedler, Madelin R.; Trexler, Eric T.; Humphries, Megan N.; Lamadrid, Priscila; Waddell, Brian; Ford, Sarah; SanFilippo, Gillian; Callahan, Kaitlin; Gegenheimer, James; Reyes, Justin; Pane, Olivia; Klahr, Daniel; et al.
Abstract : An amendment to this paper has been published and can be accessed via the original article.